COVID-19's impact on primary care and related mitigation strategies: A scoping review. Issue 1 (1st January 2021) - Lim, Jayleigh; Broughan, John; Crowley, Des; O'Kelly, Brendan; Fawsitt, Ronan; Burke, Mary Carmel; McCombe, Geoff; Lambert, John S.; Cullen, Walter
Abstract: Background: The COVID-19 pandemic has had a substantial impact on primary care throughout Europe and globally. Objectives: This review aims to ascertain how the pandemic has impacted primary care service provision/patients and to examine strategies to mitigate these impacts. Methods: The scoping review framework comprised a six-stage process developed by Arksey and O'Malley. The search process was guided by the Joanna Briggs Institute three-step search strategy and involved searching the PubMed, Embase, Scopus, CINAHL Plus, and Cochrane Library databases. The review is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. A thematic analysis approach by Braun and Clarke was used to interpret the findings. Results: Thirty-two studies from 18 countries and six continents were included, 13 reported original research, three were reviews, and 16 were case reports reporting healthcare systems' experiences of dealing with the pandemic. Emerging themes concerned the COVID-19 pandemic's impact on primary care service provision and patients, the impact of the rapid transition to telemedicine due to COVID-19 on primary care, and strategies to mitigate the impact of COVID-19 on primary care (i.e. infection prevention and control measures, alternatives/modifications to traditional service delivery or workflow, government policy responses, and education). Conclusion: The COVID-19 pandemic has considerably impacted on primary care at both service and patient levels, and various strategies to mitigate these impacts have been described. Future research examining the pandemic's ongoing impacts on primary care, as well as strategies to mitigate these impacts, is a priority.